Calibration of the APEX Model to Simulate Management Practice Effects on Runoff, Sediment, and Phosphorus Loss. Issue 6 (1st November 2017) - Bhandari, Ammar B.; Nelson, Nathan O.; Sweeney, Daniel W.; Baffaut, Claire; Lory, John A.; Senaviratne, Anomaa; Pierzynski, Gary M.; Janssen, Keith A.; Barnes, Philip L.
Abstract : Process‐based computer models have been proposed as a tool to generate data for Phosphorus (P) Index assessment and development. Although models are commonly used to simulate P loss from agriculture using managements that are different from the calibration data, this use of models has not been fully tested. The objective of this study is to determine if the Agricultural Policy Environmental eXtender (APEX) model can accurately simulate runoff, sediment, total P, and dissolved P loss from 0.4 to 1.5 ha of agricultural fields with managements that are different from the calibration data. The APEX model was calibrated with field‐scale data from eight different managements at two locations (management‐specific models). The calibrated models were then validated, either with the same management used for calibration or with different managements. Location models were also developed by calibrating APEX with data from all managements. The management‐specific models resulted in satisfactory performance when used to simulate runoff, total P, and dissolved P within their respective systems, with r 2 > 0.50, Nash–Sutcliffe efficiency > 0.30, and percent bias within ±35% for runoff and ±70% for total and dissolved P. When applied outside the calibration management, the management‐specific models only met the minimum performance criteria in one‐third of the tests. The location models had better model performance when applied across all managements compared with management‐specific models. Our results suggest that models only be applied within the managements used for calibration and that data be included from multiple management systems for calibration when using models to assess management effects on P loss or evaluate P Indices. Core Ideas: The APEX model has limited ability to simulate effects of changing management. If available, multiple management should be used to calibrate and validate the model. Policy makers must exercise caution in using model‐estimated P losses to evaluate PIs.